Evaluation of the Head Multislice Computed Tomography Scan in Emergency Department - Dijana Zadravec; Tomislav Gregurić; Mia Smoljan; Matej Mustapić; Gordana Miličić; Andrijana Jović; Danijela Rubil; Daniela Tomasović; Vanja Bašić Kes (Acta Clinica Croatica, 2017)
The aim of the study was to examine the prevalence of head injuries, acute stroke and brain tumors obtained from computed tomography (CT) scans in the emergency department (ED) during a one-year period. We also assessed the potential effect of seasons on the occurrence of stroke, head trauma and tumors found on CT scans, expressed in monthly intervals. This retrospective review included all patients that underwent emergency head CT from the hospital database. A total of 3888 head CT examinations were performed in adult patients presenting to ED and 1424 CT scans had at least one pathologic finding meeting diagnostic criteria for the study. Of the total number of CT scans analyzed, acute stroke was identified in 552 (14.19%), head trauma in 660 (16.97%), and brain tumor in 212 (5.45%) patients. Head trauma was more commonly found in males (n=465, 70.45%) than in females (n=195, 29.54%). Acute stroke was slightly more common in males than in females. Brain tumors were more frequently found in female patients. There were monthly variations in the number of head injuries and acute stroke diagnosed during the study period. Men and elderly patients were found to account for the greatest number of traumatic head injuries and therefore are at the highest risk of possible brain injury.